2016
DOI: 10.1002/lary.26111
|View full text |Cite
|
Sign up to set email alerts
|

Forgetful but not forgotten: Bathroom-related craniofacial trauma among the elderly

Abstract: 4 Laryngoscope, 127:820-827, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
2
16
1
2
Order By: Relevance
“…In this nationwide, large database analysis, falls were the most common cause of facial fracture among the American older adults, as previous studies with smaller, regional samples have suggested . Falls among older adults are considered a public health issue, as fall‐related burden and costs are rising in many countries, placing a substantial economic challenge on society .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In this nationwide, large database analysis, falls were the most common cause of facial fracture among the American older adults, as previous studies with smaller, regional samples have suggested . Falls among older adults are considered a public health issue, as fall‐related burden and costs are rising in many countries, placing a substantial economic challenge on society .…”
Section: Discussionmentioning
confidence: 66%
“…In this nationwide, large database analysis, falls were the most common cause of facial fracture among the American older adults, as previous studies with smaller, regional samples have suggested. [8][9][10][11] Falls among older adults are considered a public health issue, as fallrelated burden and costs are rising in many countries, placing a substantial economic challenge on society. 5 It is important to highlight, however, that when the data were examined to determine whether mortality rates (in ED and following in patient admission) changed over the study period, the analysis indicated that there was no significant trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also of note is that less than 2% of fractures involved the mandible, a lower figure than reported in analyses among non-nursing home cohorts and younger patients. 16,35,36 The reason for this finding, although speculative, is likely related to the mechanisms of injury noted in this population (Table). Of note, mandible fractures often require greater acceleration forces than injuries in some other common locations, such as nasal fractures; because much of the patient population in the present study has limited mobility compared with a more independent cohort, we noted largely low-velocity mechanisms of injury.…”
Section: Discussionmentioning
confidence: 91%
“…A recent comparative analysis 16 on elderly traumatic brain injury and craniofacial trauma stemming from bathroom-related falls noted that there were more than 3 million ED visits during a recent 5-year period for such injuries, with toilet transfer playing a significant role. Several suggestions for improvement were offered for prevention of these injuries 16 ; although this aforementioned study 16 offers valuable lessons, only 3.6% of facial injuries in the present analysis occurred in the bathroom setting, emphasizing important differences in mechanism of injury on comparison of older adults who live independently compared with those who reside in nursing homes (Table). Although comprising only 12.6% of injuries (Figure 2), facial fractures engender serious sequelae and can often have a significant effect on function and quality of life.…”
Section: Discussionmentioning
confidence: 99%